Effects of secondary poisoning from anticoagulant and biological rodenticides on barn owl, Tyto alba javanica, in an immature oil palm plantation - Trubus , Mohd. Na'im (2011)
The barn owl, Tyto alba javanica has been used as a biological control agent to deal with rat infestation in oil palm plantation for several decades now. However, the employment of chemical rodenticides to suppress rat population when damage increases have detrimental effects on the bird. This research was conducted with the objectives of evaluating the evidence and effects of warfarin, brodifacoum, and a biological based rodenticide, Sarcocystis singaporensis on breeding performance, ranging behavior, nestling growth and health status of barn owl. The field study was conducted in immature oil palm area in the FELCRA Seberang Perak, Malaysia from July 2008 to January 2010. From three breeding seasons of barn owls assessed, there was no significant difference in mean clutch size for untreated control plot, warfarin treated plot, brodifacoum treated plot and biorodenticide treated plot. However, the mean hatching success and the mean fledging success of barn owls in the control plot was significantly higher compared to the rodenticide treated plots. Both the hatching and fledging success in the biorodenticide treated plot was significantly higher compared to the chemical rodenticides treated plots. Also the warfarin treated plot showed a significantly higher mean hatching and fledging success compared to brodifacoum treated plot. Rat damage analysis indicated that in the control plot, rat was solely controlled by predation of barn owls contributing moderate control 24 months after the nest boxes were installed. Damage fluctuated from 4.81% to 9.78% throughout that period. Nonetheless, rat damage recorded at the end of the study was lower compared to the damage incurred at the start of the census. Baiting with S. singaporensis and warfarin were found to be effective to control rat when applied in two rounds. In contrast baiting with brodifacoum Mcan achieve satisfactory control with a single round of baiting. On the other hand it poses secondary poisoning risks to non target animals including barn owls as evidenced from the addled eggs, abandoned nest boxes and the teratogenic signs in nestlings showed in this study. Nestling growth analysis showed that nestlings in control plot were consistently heavier in body mass and longer in culmen, tarsus, wing and tail length compared to rodenticide treated plots. The culmen and tarsus length of nestlings reached that of the adult size towards the end of the growth period monitored. On the contrary, the wings and tail feathers still grew until day 49 i.e., several days to fledging and continued to grow after fledging. The mean wing and tail length in the control plot was longer by 15.26% and 18.24% respectively compared to the brodifacoum treated plot. Home range size in the control plot was smaller compared to rodenticide treated plots for both males and females during the mating and brooding periods. The home range size of females and males at the mating stage was inversely correlated to the levels of rat damage i.e., rat abundance, but only females showed a significant correlation to rat abundance (Pearson Correlation, r =-0.9844; p < 0.05), while males did not (r = -07148; p > 0.05). Home range size changed dramatically during the brooding period. At this time home range of females was not significantly correlated to rat abundance (Pearson Correlation, r = -0.8286; p > 0.05). In contrast, the home range size for males was significantly correlation to rat abundance (r =-0.9760; p < 0.05). The study also indicates that home range size of females during mating was significantly larger compared to during brooding (t-test; p<0.05). The males exhibited a significantly larger home range size during brooding compared to the period of the onset of mating (t-test;p<0.01). Warfarin and brodifacoum residues were found in the food of barn owls only during and one month after baiting campaign. Out of the 91 pellets recovered from the warfarin treated plot, 25.27% (n= 23) contained warfarin residue ranging from 0.034 to 2.826 μg/g wet weight. Of the 99 pellets collected from the brodifacoum plot, 24.24% (n=24) contained brodifacoum residue ranging from 0.011 to 1.156 g/g wet weight. Of 18 eggs collected in warfarin treated plot 61.11% (n=11), contained warfarin residue ranging from 0.007 to 0.332 ug/g wet weight. Of the 18 eggs collected in brodifacoum treated plot, 66.67% (n=12) contained brodifacoum residue ranging from 0.04 to 0.0615 ug/g wet weight. No pellets and eggs recovered from the control and biorodenticide treated plot detected to contain warfarin and brodifacoum residue. The study showed that rodenticide residues can be transferred to egg and decrease eggshell mass and lead to thinning of eggshell of barn owls.